Kejelasan Sasaran Anggaran, Pengendalian Akuntansi, Dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah Kabupaten Gorontalo - Saprudin . (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
The objectives of this study are (1). Analyzing the clarity of budget targets has a positive effect on the accountability of performance of the Gorontalo district government. (2). Analyzing accounting controls has a positive effect on the accountability of the performance of Gorontalo District government. (3). Analyzing the reporting system has a positive effect on the accountability of the performance of the Gorontalo district government. Research Results Show That Clarity of Budget Objectives Has Positive and Significant Effects on Performance Accountability of Local Government Agencies. Clarity of budget targets has a positive and significant effect on the accountability of performance of regional agencies. Accounting control has a positive and significant effect because accounting controls can help improve local government transparency, especially in providing information on the activities and financial performance of local governments. In addition, accounting control seen from the budget realization report has provided information on the financial performance of the local government, because the budget realization report is clearly visible. That is, accounting controls held by the government play a role in increasing accountability for performance. The Reporting System Has Negative and Significant Effects on Performance Accountability of Local Government Agencies. The reporting system has a negative and insignificant effect because the reporting system has not been able to provide information in implementing the budget that has been set and also in the world of government.